Chemical Composition and Pulp Properties of Abaca (Musa textilis N’ee) cv. Inosa Harvested at Different Stages of Stalk Maturity - Moreno, Luz O.; Protacio, Calixto M. (Annals of Tropical Research, 2012)
Given the increasing global demand for pulp, there is a need to look into the prospects of increasing fiber production and shortening the harvesting cycle of abaca without sacrificing the quality of fibers for pulp production. This study investigated the chemical and pulp properties of abaca cv. Inosa fibers harvested at different stages of stalk maturity to determine their suitability for pulp and paper production. Fibers obtained from 8-10-month-old (immature) abaca cv. Inosa possessed the desirable chemical properties for pulping, namely; low lignin and ash content, high alpha-cellulose, holocellulose and hemi-cellulose contents; which are comparable with those obtained from intermediate and mature stalks. The average pulp yield, Kappa number, viscosity, tear index and breaking length of pulps from immature stalks were already comparable with those of mature fibers and were even higher than the mature fibers of Linawaan and Laylay cultivars. Fibers of abaca cv. Inosa obtained from immature stalks were thus, found suitable for pulp and paper production.